A Semantic Analysis of Denotative and Connotative Meaning in User-Generated Content Across Instagram - Casandra Dealova Sitopu; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aimed to analyze the denotative and connotative meanings in Instagram captions as a form of user-generated content. The problem addressed in this study was how literal and implied meanings are used in digital communication. This research used a descriptive qualitative method with a semantic analysis approach. The data were taken from five Instagram captions posted by public figures. The findings show that connotative meaning is more dominant than denotative meaning. Short captions can convey complex meanings through metaphor, symbolism, and ambiguity. It is concluded that meaning in social media, especially Instagram, is flexible and highly influenced by context and user interpretation.